Tunnels - Modan, Rutu (Drawn & Quarterly, 2021)
"When a great antiquities collector is forced to donate his entire collection to the Hebrew University in Jerusalem, Nili Broshi sees her last chance to finish an archeological expedition begun decades earlier--a dig that could possibly yield the most important religious artifact in the Middle East. Motivated by the desire to reinstate her father's legacy as a great archeologist after he was marginalized by his rival, Nili enlists a ragtag crew--a religious nationalist and his band of hilltop youths, her traitorous brother, and her childhood Palestinian friend, now an archeological smuggler. As Nili's father slips deeper into dementia, warring factions close in on and fight over the Ark of the Covenant! Backed by extensive research into this real-world treasure hunt, Modan sets her affecting novel at the centre of a political crisis. She posits that the history of biblical Israel lies in one of the most disputed regions in the world, occupied by Israel and contested by Palestine. Often in direct competition, Palestinians and Israelis dig alongside one another, hoping to find the sacred artifact believed to be a conduit to God. Two time Eisner Award winner Rutu Modan's third graphic novel, Tunnels, is her deepest and wildest yet. Potent and funny, Modan reveals a Middle East caught up in the past while trying to inch ever forward."--